PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY PADA PERSEPSI INVESTOR DENGAN PROFITABILITAS DAN KEPEMILIKAN MANAJEMEN SEBAGAI VARIABEL PEMODERASI - Pratiwi, Luh Winda (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2016)
ABSTRACT This study aims to test the effect of CSR (Corporate Social Responsibility) disclosure on investor’s perception using profitability and management’s ownership as moderating variables. Populations of this study are firms listed in Indonesian Stock Exchange in 2012. The sampling technique used is purposive sampling therefore there are 118 firms used in analysis. The hypothesis is tested using the interaction test Moderated Regression Analysis. Based on the analysis results, it can be concluded that CSR disclosure has no effect on investor’s perception. Profitability moderate the effect of CSR disclosure on investor’s perception while management’s ownership can not moderate the effect of CSR disclosure on investor’s perception. Keywords: investor’s perception, corporate social responsibility disclosure, profitability, management’s ownership
Keywords: persepsi investor; pengungkapan corporate social responsibility; profitabilitas; kepemilikan manajemen